A novel strain of Levilactobacillus brevis PDD-5 isolated from salty vegetables has beneficial effects on hyperuricemia through anti-inflammation and improvement of kidney damage - Jue Xu; Maolin Tu; Xiankang Fan; Yuxing Guo; Tao Zhang; Xiaoqun Zeng; Zhendong Cai; Zhen Wu; Daodong Pan (Food Science and Human Wellness)
Hyperuricemia is a metabolic disorder caused by abnormal purine metabolism, resulting in abnormally high serum uric acid. In this study, a novel Levilactobacillus brevis PDD-5 isolated from salty vegetables was verified with the function of alleviating hyperuricemia. The relevant effects of L. brevis PDD-5 in lowering uric acid were analyzed by in vitro and in vivo experiments. The results showed that the L. brevis PDD-5 has (68.86 ± 15.46)% of inosine uptake capacity and (95.75 ± 3.30)% of guanosine uptake capacity in vitro. Oral administration of L. brevis PDD-5 to hyperuricemia rats reduced uric acid, creatinine, and urea nitrogen in serum, as well as decreased inosine and guanosine levels in the intestinal contents of rats. Analysis of relevant markers in the kidney by ELISA kits revealed that L. brevis PDD-5 alleviated oxidative stress and inflammation. Moreover, the gene expression of uric acid transporter 1 (URAT1) and glucose transporter 9 (GLUT9) was down-regulated, and the gene expression of organic anion transporter 1 (OAT1) was up-regulated after treatment with L. brevis PDD-5. Western blot analysis showed that L. brevis PDD-5 alleviated hyperuricemia-induced kidney injury through the NLRP3 pathway. These findings suggest that L. brevis PDD-5 can lower uric acid, repair kidney damage, and also has the potential to prevent uric acid nephropathy.